Reconfiguration Techniques for Self-X Power and Performance Management on Xilinx Virtex-II/Virtex-II-Pro FPGAs. (4th January 2011) - Schuck, Christian; Haetzer, Bastian; Becker, Jürgen
Abstract : Xilinx Virtex-II family FPGAs support an advanced low-skew clock distribution network with numerous global clock nets to support high-speed mixed frequency designs. Digital Clock Managers in combination with Global Clock Buffers are already in place to generate the desired frequency and to drive the clock networks with different sources, respectively. Currently, almost all designs run at a fixed clock frequency determined statically during design time. Such systems cannot take the full advantage of partial and dynamic self-reconfiguration. Therefore, we introduce a new methodology that allows the implemented hardware to dynamically self-adopt the clock frequency during runtime by reconfiguring the Digital Clock Managers. We also present a method for online speed monitoring which is based on a two-dimensional online routing. The created speed maps of the FPGA area can be used as an input for the dynamic frequency scaling. Figures for reconfiguration performance and power savings are given. Further, the tradeoffs for reconfiguration effort using this method are evaluated. Results show the high potential and importance of the distributed dynamic frequency scaling method with little additional overhead.